Criminalisation and Advanced Marginality : Critically Exploring the Work of Loïc Wacquant - Lea, John; Squires, Peter, 1958- (Book collections on Project MUSE., 2012)
This text presents a critical but constructive review and development of the challenging work of Loïc Wacquant particularly focusing on the governance of crime and disorder welfare, change inequality and diswelfare.